1983
DOI: 10.1111/j.1365-2621.1983.tb10803.x
|View full text |Cite
|
Sign up to set email alerts
|

A Diffusion Model with a Concentration‐Dependent Diffusion Coefficient for Describing Water Movement in Legumes During Soaking

Abstract: A mathematical model based on Fick's diffusion equation with a concentration-dependent diffusion coefficient was proposed to describe the absorption of water by legumes. The equation was solved by using a numerical scheme. Parameter study was performed. The model is capable of predicting sigmoidal-shaped water uptake curves common to many legumes. Differences are discussed between the surface resistance boundary condition used in this study and the radiation boundary condition widely used for dehydration calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 15 publications
2
98
2
Order By: Relevance
“…Higher temperatures are known to expand and soften grains (KASHANINEJAD et al, 2007). Several studies have shown that increasing the temperature of the soaking medium is an excellent way to accelerate the water absorption of various seeds, reducing the soaking time (QUAST; DA SILVA, 1977;KON, 1979;OBEKPA, 1990;ABU-GHANNAM;MCKENNA, 1997;TANG;SOKHANSANJ;SOSULSKI, 1994;HUNG et al, 1993;SEYHAN-GÜRTAS;AK;EVRANUZ, 2001;HSU, 1983a;MASKAN, 2002). The moisture content of the grains during hydration can be directly related to two variables: time and temperature.…”
Section: Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher temperatures are known to expand and soften grains (KASHANINEJAD et al, 2007). Several studies have shown that increasing the temperature of the soaking medium is an excellent way to accelerate the water absorption of various seeds, reducing the soaking time (QUAST; DA SILVA, 1977;KON, 1979;OBEKPA, 1990;ABU-GHANNAM;MCKENNA, 1997;TANG;SOKHANSANJ;SOSULSKI, 1994;HUNG et al, 1993;SEYHAN-GÜRTAS;AK;EVRANUZ, 2001;HSU, 1983a;MASKAN, 2002). The moisture content of the grains during hydration can be directly related to two variables: time and temperature.…”
Section: Hydrationmentioning
confidence: 99%
“…It can be observed that at all temperatures, water uptake was faster in the initial stages, especially in the first four hours, and gradually slowed down as the moisture content approached saturation. According to Hsu (1983a), it had been demonstrated that diffusion in the solid endosperm is the main mechanism that controls the rate of absorption in seeds regardless of the process conditions. There was a significant effect of temperature on the grain moisture (p ≤ 0.05), mainly on the dynamic of hydration isotherms and also on the equilibrium moisture of the five cultivars.…”
Section: Hydration Processmentioning
confidence: 99%
“…Phenomenological models consider the elementary steps of mass transfer by diffusion (Fan et al, 1962;Hsu, 1983).…”
Section: Phenomenological Modelsmentioning
confidence: 99%
“…Water uptake behavior cannot solely be linked to seed coat thickness. Seed size has also been linked to water uptake behavior (Arechavaleta-Medina and Synder, 1981;Hsu et al, 1983a;Seyhan-Gurtas et al, 2001). As water uptake is determined via mass uptake such that a smaller seed would exhibit a proportionally greater increase in water mass uptake than a larger seed if both were taking up water at the same rate.…”
Section: Factors Affecting Water Uptakementioning
confidence: 99%
“…no lag) can be considered well hydrating seeds. For example, seeds like peas (yellow, green and Marrowfat), navy beans, kidney beans, chickpeas, lentils, and most soybeans have been noted to possess rapid water uptake and do not possess a lag period prior to imbibition Abu-Ghannam & McKenna, 1997;Hsu, 1983a;Hsu, 1983b;Liu et al, 2005;Meyer et al, 2007;Ross et al, 2008;Seyhan-Gurtas et al, 2001). However some pulses like pinto beans, black beans, dried green beans, red beans possess a significant lag period prior to the initiation of water uptake (Liu et al, 2005;Ross et al, 2008).…”
Section: Variations In Water Uptake Behavior In Pulse Seedsmentioning
confidence: 99%